The Potential of Air-Sparged Hydrocyclone Flotation in Environmental Technology - J. D. Miller (The Minerals, Metals and Materials Society, 1993)
Air-sparged hydrocyclone (ASH) flotation is a high-capacity flotation technology originally developed in the Department of Metallurgical Engineering at the University of Utah for processing mineral resources. However, the technology has been found to be useful in industrial waste processing, in the recycle of secondary resources, and in remediation of environmental problems. For example, areas in which the ASH technology is expected to have potential application include cleaning of waste coal fines, air stripping to remove volatile organics from drinking and process water, water disinfection by ozone or chlorine sparging, dispersed oil removal from water, and contaminated soil remediation. Recently, the ASH has been studied extensively for deinking flotation in the wastepaper recycling industry and has been shown to have excellent efficiency/capacity. In fact, a 20-million-dollar plant has been in operation since June 1992. The ASH technology can provide a specific capacity hundreds of times more than that which can be achieved with conventional flotation equipment and in certain instances is expected to provide superior separation efficiencies when compared to other technologies. The design and principles of ASH flotation are described. Experimental data for fine coal flotation, volatile organics stripping, and deinking flotation for paper recycle are presented and discussed. Finally, other potential areas of application for environmental technology are considered.